Learning English as a Second Language: Earlier is Better : - Wallin, Jamie; Cheevakumjorn, Boonsri (Universitas Muhammadiyah Sidoarjo, 2020)
This study reviews recent evidence concerning childhood bilingualism: what is the optimal age to begin learning a second language? Acquiring a first language is mainly unconscious and begins at birth. A bilingual child is one who has acquired a second language simultaneously or is acquiring a second language sequentially. Research evidence confirms that second language acquisition should begin as early as possible. It requires a holistic approach in which learners are immersed in the sounds and daily experiences of the second language, much in the same way as the first language was acquired. It is during the very early years of a child’s life that brain development is most receptive to acquiring linguistic competence in one or more additional languages. Evidence is clear that younger-age learners will have better accents and a more diversified vocabulary than those who are older. Thus, creating an immersion-like environment is essential for schools which aim to develop sequential bilinguals. Elements for successful English as a second language programmes are identified, with supporting research evidence. HIGHLIGHTS: When young bilinguals ‘borrow’ words from the other language could be regarded as being very resourceful, not confused. Children from lower socioeconomic backgrounds may lack certain linguistic experiences in terms of vocabulary size, and lack of exposure to books, conversation practice, or first-hand life experiences.